Computational modeling of cambium activity provides a regulatory framework for simulating radial plant growth - Lebovka, Ivan; Hay Mele, Bruno; Liu, Xiaomin; Zakieva, Alexandra; Schlamp, Theresa; Gursanscky, Nial Rau; Merks, Roeland MH; Großeholz, Ruth; Greb, Thomas (eLife, 2023)
Precise organization of growing structures is a fundamental process in developmental biology. In plants, radial growth is mediated by the cambium, a stem cell niche continuously producing wood (xylem) and bast (phloem) in a strictly bidirectional manner. While this process contributes large parts to terrestrial biomass, cambium dynamics eludes direct experimental access due to obstacles in live-cell imaging. Here, we present a cell-based computational model visualizing cambium activity and integrating the function of central cambium regulators. Performing iterative comparisons of plant and model anatomies, we conclude that the receptor-like kinase PXY and its ligand CLE41 are part of a minimal framework sufficient for instructing tissue organization. By integrating tissue-specific cell wall stiffness values, we moreover probe the influence of physical constraints on tissue geometry. Our model highlights the role of intercellular communication within the cambium and shows that a limited number of factors are sufficient to create radial growth by bidirectional tissue production.